Key Data Record and Analysis for Traction Converter of High-speed Trains - YIN Zhenhuan; DONG Kan; GAO Jilei (机车电传动)
In order to ensure the safety of high-speed trains and satisfy the demand of development and maintenance of traction converters, a key data record and analysis system was developed. Based on a standard CPCI-6U board, analog and digital parameters could be collected, recorded and downloaded through Ethernet, and analyzed on PC. The proposed system had be applied in several EMU traction converters, and provided precise field data for actual fault analysis, which was an important base for development and maintenance of the traction converter.